Menemukan Damai di Tengah Badai Digital: Bimbingan Pastoral Konseling untuk Mengatasi Doomscrolling - Brek, Yohan; Sapoh, Fani (PT. Giat Konseling Nusantara, 2024)
In the digital era, technological developments have had a significant impact on access to information, especially through the doomscrolling phenomenon. Affects an individual's ability to live daily life effectively. This research aims to examine the psychological impact of doomscrolling and explore the role of pastoral counselors in helping individuals overcome the negative impacts of this habit. Using a qualitative descriptive approach, the research collected data through literature reviews, academic articles, case studies, and interviews with pastoral counselors and individuals affected by doomscrolling. Thematic analysis identified key patterns and themes related to this phenomenon, while data validation techniques ensured the accuracy and reliability of the findings. The results showed that doomscrolling had a significant impact on psychological well-being, including increased anxiety, depression and sleep disturbances. Pastoral counselors can help individuals develop strategies to overcome these negative impacts through a holistic approach that includes empathetic listening, healthy boundary development, and spiritual formation. Religious community support has also proven important in providing a sense of community and social connection that helps individuals deal with the negative impacts of doomscrolling. Building resilience through pastoral guidance enables individuals to manage stress more effectively and maintain their mental and spiritual well-being amidst digital challenges.